Unveiling Movie Dialogue through Speech Acts: A Pragmatic Analysis of Aquaman and the Lost Kingdom - Nisa, Baiatun; Naomisa, Rahmi (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
This study investigates the use of speech acts in cinematic dialogue, focusing on the 2023 film Aquaman and the Lost Kingdom. Employing a qualitative descriptive approach, the research categorized 137 speech acts based on Searle’s taxonomy: representatives, directives, expressives, commissives, and declaratives. The findings revealed that representative acts were dominant in the dialogue (60.58%), followed by directives (24.82%), expressives (8.03%), commissives (4.38%), and declaratives (2.19%). These results indicate that cinematic narratives heavily rely on exposition, action-driven communication, emotional engagement, relational commitments, and performative declarations to construct character development and advance the storyline. The analysis highlights the strategic use of speech acts to reflect character intentions and social dynamics within the film. By extending speech act theory into cinematic discourse, this study contributes to the growing field of media pragmatics. It suggests the pedagogical potential of film dialogues as authentic material for teaching pragmatic competence in English as a Foreign Language (EFL) contexts. While the study was limited to a single film and excluded multimodal elements, it provided a foundation for further research integrating verbal and nonverbal aspects of communication across diverse media genres. Overall, the findings affirm the importance of pragmatic analysis in understanding contemporary narrative media and open new pathways for interdisciplinary exploration between linguistics, media studies, and language education.